Pengaruh Employee Engagement Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan PT. Perkebunan Nusantara IV Regional Iii Kebun Sei Tapung - Hery Walmen Manalu; Khairunnisak Khairunnisak (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine and analyze the effect of employee engagement and non-physical work environment on the performance of employees at PT. Perkebunan Nusantara IV Regional III Kebun Sei Tapung. Employee engagement and non-physical work environment are two factors that have varying effects on employee performance. The research method used is a quantitative approach with data collection techniques through questionnaires given to 86 employee respondents at PT. Perkebunan Nusantara IV Regional III Kebun Sei Tapung. The results show that employee engagement has a positive and significant effect on employee performance, as indicated by a t-value of 5.989 > t-table 1.988 and sig 0.001 < 0.05. The non-physical work environment also has a positive and significant effect on employee performance, with a t-value of 5.154 > t-table 1.988 and sig 0.001 < 0.05. Simultaneously, both variables have a significant effect on performance with an F-value of 63.569 > F-table 3.11 and sig 0.001 < 0.05. The Adjusted R Square value of 0.596 indicates that 59.6% of employee performance variation is explained by the two independent variables, while 40.4% is influenced by other factors outside the model. The results of this study show that employee engagement and non-physical work environment are important factors that can improve employee performance, both partially and simultaneously. Therefore, companies are advised to strengthen support, communication, working relationships, and create a comfortable and conducive working environment.